Fall of Giants? : Why the Memory World Champion Must Reinvent Itself (KULT_online, 2024)
Who belongs to German society, what belongs to German history, and who is allowed to speak out about it? These questions are explored in the edited volume. Contributions engage with the negotiation of German memory culture and its identity-forming effect. With its diverse and varied perspectives, the volume calls for a more inclusive understanding of history and a broadening of memory culture to reflect Germany as a country of immigration – a "Zeitenwende" in the politics of memory towards multidirectional memory.